Cognitive Stress Reduces the Effect of Levodopa on Parkinson's Resting Tremor. (10th January 2017) - Zach, Heidemarie; Dirkx, Michiel F.; Pasman, Jaco W.; Bloem, Bastiaan R.; Helmich, Rick C.
Summary: Aims: Resting tremor in Parkinson′s disease (PD) increases markedly during cognitive stress. Dopamine depletion in the basal ganglia is involved in the pathophysiology of resting tremor, but it is unclear whether this contribution is altered under cognitive stress. We test the hypothesis that cognitive stress modulates the levodopa effect on resting tremor. Methods: Tremulous PD patients (n = 69) were measured in two treatment conditions (OFF vs. ON levodopa) and in two behavioral contexts (rest vs. cognitive co‐activation). Using accelerometry, we tested the effect of both interventions on tremor intensity and tremor variability. Results: Levodopa significantly reduced tremor intensity (across behavioral contexts), while cognitive co‐activation increased it (across treatment conditions). Crucially, the levodopa effect was significantly smaller during cognitive co‐activation than during rest. Resting tremor variability increased after levodopa and decreased during cognitive co‐activation. Conclusion: Cognitive stress reduces the levodopa effect on Parkinson's tremor. This effect may be explained by a stress‐related depletion of dopamine in the basal ganglia motor circuit, by stress‐related involvement of nondopaminergic mechanisms in tremor (e.g., noradrenaline), or both. Targeting these mechanisms may open new windows for treatment. Clinical tremor assessments under evoked cognitive stress (e.g., counting tasks) may avoid overestimation of treatment effects in real life.